2015
DOI: 10.1002/nau.22741
|View full text |Cite
|
Sign up to set email alerts
|

The role of intravesical prostatic protrusion (IPP) in the evaluation and treatment of bladder outlet obstruction (BOO)

Abstract: Compared to other modalities, the advantage of IPP in assessing BOO may be its easy applicability and non-invasive nature. Therefore, there is a consideration for a larger role of IPP in bedside assessment and management of BOO in daily practice. Neurourol. Urodynam. 35:535-537, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 17 publications
1
26
0
2
Order By: Relevance
“…32 1.6 | Developments in LUTS assessment 1.6.1 | Imaging techniques Multiple imaging techniques with or without flow parameters have been developed over recent decades to potentially diagnose BOO ( Table 1). [33][34][35][36] The best described techniques are Detrusor (or Bladder) Wall Thickness (DWT/BWT), estimated bladder weight, prostate transitional zone volume, and intravesical prostate protrusion (PP). All techniques are generally compared to the current gold standard to define BOO, namely pressure-flow studies and their diagnostic performance is detailed in Table 1.…”
Section: Prostate Size Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…32 1.6 | Developments in LUTS assessment 1.6.1 | Imaging techniques Multiple imaging techniques with or without flow parameters have been developed over recent decades to potentially diagnose BOO ( Table 1). [33][34][35][36] The best described techniques are Detrusor (or Bladder) Wall Thickness (DWT/BWT), estimated bladder weight, prostate transitional zone volume, and intravesical prostate protrusion (PP). All techniques are generally compared to the current gold standard to define BOO, namely pressure-flow studies and their diagnostic performance is detailed in Table 1.…”
Section: Prostate Size Measurementmentioning
confidence: 99%
“…Multiple imaging techniques with or without flow parameters have been developed over recent decades to potentially diagnose BOO (Table ) . The best described techniques are Detrusor (or Bladder) Wall Thickness (DWT/BWT), estimated bladder weight, prostate transitional zone volume, and intravesical prostate protrusion (PP).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is invasive, time-consuming, and costly. Therefore, it is generally indicated for patients who are not responsive to initial conservative treatment or pharmacotherapy, patients with previous intervention, and those of extreme age range and equivocal cases [11]. That being said, we find it imperative that diagnosis of IPP be confirmed by transabdominal ultrasonography (TAUS) or TRUS of the prostate before proceeding with any sort of medical or surgical management.…”
Section: Clinical Evaluation and Managementmentioning
confidence: 99%
“…Clinical studies have demonstrated that IPP can identify BOO. IPP has shown a positive predictive value of 72% for BOO [11]. In fact, the positive predictive value of the combined parameters IPP and resistive index of the prostatic capsular artery increases to 83.8% [12].…”
Section: Pathophysiology and Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation